The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1007/s00586-010-1637-x
|View full text |Cite
|
Sign up to set email alerts
|

Rib length asymmetry in thoracic adolescent idiopathic scoliosis: is it primary or secondary?

Abstract: The development of scoliosis in animal models after inducing asymmetric rib growth suggests the possible role of asymmetric rib growth in the etiopathogenesis of adolescent idiopathic scoliosis (AIS). Asymmetric rib length is well recognized in idiopathic scoliosis; however, whether this rib asymmetry is primary or secondary has not been clearly documented. The objectives of this study were to investigate any rib length asymmetry in patients with AIS and compare those with scoliosis with syringomyelia (SS) wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 23 publications
2
11
0
1
Order By: Relevance
“…Two studies have looked at the differences of left and right rib length in spine deformity patients. Zhu et al [3] analyzed patients with adolescent idiopathic scoliosis and syringomyelia, with the length of selected ribs measured from spiral computed tomography (CT) scans. They noted a difference of 4e7 mm in rib length compared with ribs above and below the apex, which also correlated to the Cobb angle of the thoracic curve.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies have looked at the differences of left and right rib length in spine deformity patients. Zhu et al [3] analyzed patients with adolescent idiopathic scoliosis and syringomyelia, with the length of selected ribs measured from spiral computed tomography (CT) scans. They noted a difference of 4e7 mm in rib length compared with ribs above and below the apex, which also correlated to the Cobb angle of the thoracic curve.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies have described abnormalities of rib or thorax growth and asymmetry in children with scoliosis [1][2][3][4][5]. Rib deformities created in experimental animals have demonstrated that abnormal thoracic development is a common feature of scoliosis [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Further studies are necessary to form physiotherapeutic programs to prevent increasing compensations and other secondary deformations such as ribs asymmetry (Zhu et al, 2011) or the temporomandibular joints dysfunctions (Smieciuch, 2011). Another goal is to concentrate on the improvement of gait pattern in persons with idiopathic scoliosis as long as the modern physiotherapy has appropriate means to facilitate gait in patients with different pathology (Adler et al, 2008) including scoliosis.…”
Section: Resultsmentioning
confidence: 99%
“…• in the trunk - breasts [32,33], ribs [34-39], chest wall blood supply [40,41], and iliac height [42,43];…”
Section: Introductionmentioning
confidence: 99%